Akuntansi Manajemen: Peran Sistem Informasi dan Budaya Organisasi - Surya Maulana, Drajad (Jurnal Etnik: Ekonomi-Teknik, 2022)
In the current era, information plays a very important role in various aspects of human life individually or in organizations. Information is able to help an organization reach its optimal point, the effectiveness of information makes it easier to identify competitors and analyze the profits of other competitors. One of the factors that can influence this information system is organizational culture. The quality of an information system is influenced by the organizational culture. The purpose of this study is to determine the role of information systems and organizational culture in management accounting. The type of research used is qualitative with descriptive analysis. The data collection was carried out by means of a literature study. Based on the results of the study, it shows that information systems and organizational culture have a role in management accounting. This information system can provide information related to financial reports that are used in measuring several company activities. Accounting information systems can also play a role as a source of information that is used as a basis for consideration in making decisions for management. Culture within the company is able to influence the effectiveness of implementing accounting information systems, in which corporate culture is able to shape the behavior of managers in making decisions. The successful implementation of accounting information systems needs to pay attention to organizational factors.